The Malayan Emergency: Essays on a Small, Distant War, by Souchou Yao. Copenhagen: NIAS Press, 2016, 178 pp. - Wong Yee Tuan, (Kajian Malaysia, 2017)
The Malayan Emergency lasting from 1948 to 1960 has merited much scholarly attention since the mid-1950s. We now have a prodigious literature concerning the communist insurgency in Malaya. Having such considerable coverage already given to the topic, what does this new book add to what is already known about the communist struggle?